Comparison of the SureX® HPV genotyping test with the Digene Hybrid Capture® 2 test in cervical cancer screening - Sun, Hehao; Wang, Hong; Liu, Yin; Xu, Huifang; Chen, Peipei; Sun, Xingai; Li, Mengjie; Li, Peiyao; Li, Kunyao; Zheng, Liyang; Zhang, Shaokai (Frontiers in Oncology, 2025)
IntroductionCervical cancer, predominantly caused by high-risk human papillomavirus (HR-HPV) infections, is a critical public health issue. Effective screening is essential. This study compares the SureX® HPV genotyping test, which detects 25 HPV types, with the widely used Digene Hybrid Capture® 2 (HC2) test, which targets 13 HR-HPV types, to determine their effectiveness in cervical cancer screening among Chinese women.MethodsFrom September to December 2016, women aged 21–64 years in Shanxi Province were screened for cervical cancer using both SureX® HPV and HC2 tests. Women with abnormal cytology test would be referred for colposcopy and biopsied if necessary. Concordance rates and kappa coefficients were calculated to analyze the concordance between the two tests. Sensitivity and specificity for detecting cervical intraepithelial neoplasia grade 2 and higher (CIN2+) cases of the two tests were calculated.ResultsAmong 3028 subjects analyzed in this study, the positive rate of the common set of 13 HR-HPV types for the SureX® HPV test was 15.0%, slightly higher than HC2 test’s 13.5%. The overall concordance rate was 93.9% (95% CI: 92.95%-94.66%), with a kappa coefficient of 0.749 (0.715-0.783). Both tests demonstrated a sensitivity of 80.00% (54.81%-92.95%) for detecting CIN2+, with specificities of 85.30% (83.99%-86.52%) for SureX® HPV and 86.82% (85.57%-87.98%) for HC2. For CIN3+ detection, both tests had 100% (67.56%-100%) sensitivity, with specificities of 85.20% (83.89%-86.42%) for SureX® HPV and 86.72% (85.46%-87.89%) for HC2.DiscussionThe SureX® HPV test exhibited excellent concordance with HC2 in detecting the common 13 HR-HPV types and similar sensitivity for identifying CIN2+ cases. Its broader capability to detect 25 HPV genotypes positions it as a promising option for cervical cancer screening.